82 A Case of Recurrent Calcifying Aponeurotic Fibroma of the Hand: Managing a Rare Hand Tumour in an Evolving Healthcare Landscape. (4th May 2021) - Gallagher, M; Cooper, L; Mata, J I
Abstract: Introduction: Calcifying Aponeurotic Fibroma (CAF) is a rare benign tumour originating from the aponeuroses of tendons and their bony insertions. Our case illustrates the technical challenges and considerations of removing a large, recurrent CAF of the hand. Case Report: A 15-year-old student presented to his GP with a one-year history of a progressively enlarging painless swelling on the dorsum of the middle phalanx of the left middle finger. Plain radiographs identified a calcified soft tissue swelling with no bony involvement. The lesion was excised by the local paediatric orthopaedic service and recurred rapidly. Histology confirmed the diagnosis. He was referred to our specialist hand surgery service and the lesion was excised with the overlying skin (which demonstrated histological but not clinical disease). At six months, there was no clinical evidence of recurrence. Conclusions: CAF may present atypically, and a high index of suspicion is warranted with calcified soft tissue hand lesions. Excision with conservative margins, and we newly suggest, the overlying skin, is recommended to preserve hand function but minimise recurrence (very common). Hand surgery provision in the UK is changing with adoption of the hub and spoke model and hand tumours may be more appropriately managed at specialist centres.